KAPASITAS KELEMBAGAAN DALAM PENGEMBANGAN DESA WISATA (STUDI KASUS: DESA WISATA KETENGER, BANYUMAS) - Gita Ratri Prafitri; Maya Damayanti (Jurnal Pengembangan Kota, 2016)
Desa Wisata Ketenger is one of the oldest tourism village in Banyumas and has a lot of potential to be developed. According to Head of Youth, Sports, Culture and Touris Department in Banyumas, only two of six tourism villages in Banyumas is worth visit by tourists ie Desa Wisata Ketenger and Desa Wisata Dawuhan. It is influenced by the ability or capacity Pokdarwis as management of a tourism village in enhancing the knowledge and skills of the community through programs. The objective of this study is to determine the institutional capacity in development of Desa Wisata Ketenger. Capacity that will be researched include individual capacity and organizational capacity. The research was conducted using qualitative descriptive. Data were obtained through interviews and field observations. Results from this study indicate that in level of organization, organization has shown a good capacity in the aspect of external partnerships, aspects of tourism potential development, as well as aspects of tourism village promotion.Unfortunately, POKDARWIS "Ketenger Adventure" are less of ability to show a good capacity in leadership and coordination aspect, While at the individual level, there are good capacity in pioneering the development of tourism potential. Individuals have enough capacity in the management of tourist attractions, souvenir management, as well as service to the tourists. However, individuals have less capacity both in the understanding and application of the concept of integrated tourism village. To improve the ability at the level of individuals and organizations, Desa Wisata Ketenger have gained capacity building programs that held both of the Department of Tourism and besides offices.